Implementation of the pull levelling project in a car radio assembly firm - Afonso, Celina (2009)
This paper presents some results from the implementation of pull levelling strategy between the final assembly lines and the Original Equipment Manufacturing (OEM) clients of a car radio assembly firm. In order to respond quickly to the clients the firm maintained a stock level of, approximately, ten days of finished product for each client. This implies high costs for the firm. The implementation of the pull levelling strategy reduced these costs and increased the flexibility approaching the production to the demand, in quantity and in diversity, required by the clients. Additionally, this implementation permitted the detection of deviation, identification of problems, creation of standards and continuous improvement, stabilization of the upstream processes and the reduction of components stock. The performance indicators used by the firm to measure the performance of this implementation were the fulfillment (the achievement of the production levelling plan supplied by the Production Planning Department), the stock level, the Every Part Every Interval (EPEI) number and LIWAKS (accomplishment of the due date negotiate with the client).